Peran Katekese dalam Mewartakan Injil di Tengah Keberagaman Agama dan Budaya - Margareta Vera Lema; Monica Innanda Chiaralazzo; Intansakti Pius X (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the role of catechesis in proclaiming the Gospel amidst the religious and cultural diversity of Indonesian society. The background of this study stems from the reality of pluralism, which is both a source of richness and a challenge in social and religious life, often giving rise to potential conflicts, prejudices, and exclusive attitudes. Therefore, an approach to faith formation is needed that not only focuses on doctrinal teaching but is also capable of fostering a dialogical, tolerant, and open attitude. This study employs a qualitative method using a literature review approach through the analysis of various theological literature, scholarly articles, and relevant Church documents. The research findings indicate that catechesis plays a strategic role as a means of contextual Gospel proclamation, particularly through dialogical and inculturative approaches. Catechesis not only helps the faithful understand the teachings of the faith more deeply but also encourages them to live out and implement Gospel values in daily life within a multicultural society. Furthermore, a dialogical approach to catechesis fosters harmonious interfaith relations through mutual respect, open communication, and cooperation in social life. The inculturative approach in catechesis has also proven effective in bridging faith and culture, ensuring that the Gospel message is received without eroding local cultural identity. The implications of this research emphasize.